Comparison of computed tomography bone mineral density (BMD) with vitamin D levels - Khan, Hafiza Ammara; Akhtar, Muhammad (Medical Journal of South Punjab, 2025)
Objective: To compare the CT-bone mineral density (CT-BMD) with the vitamin D levels Methodology: A cross-sectional study was conducted from April 1st, 2023, to March 31st, 2024, at the Radiology Department, CMH Bahawalpur. One hundred patients presenting with bone pain who were referred to the radiology department for CT-BMD were included in the study. After baseline characteristics, vitamin D levels (25-OHD) were measured and categorized as ?30 ng/mL as normal, 21-29 ng/mL insufficient, and ?20 ng/mL as deficient. BMD was measured using computed tomography of the lumbar spine at L1-L4. A T-score of > -1 was considered normal, between -1 and -2.5 as osteopenia and < -2.5 as osteoporosis. Results: The mean age of the patients was 55.05±10.54 years, comprised of 31% males. The mean BMI was 26.17±3.20. The mean vitamin D level among patients was 22.22±10.35, with 59.0% as deficient, while the mean CT BMD was -1.85±1.14, with 29.0% with osteoporosis. However, about 11% of patients with osteoporosis had normal vitamin D levels. Both variables had a significant association when vitamin D was compared with CT-BMD (p<0.001). When data was stratified, normal BMI patients, overweight, and rural residents had no significant effect on the association. Conclusion: Our study concluded that CT BMD-reported osteoporosis is significantly associated with deficient vitamin D levels.